2001
DOI: 10.1046/j.1471-4159.2001.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT2A and D2 receptor blockade increases cortical DA release via 5‐HT1A receptor activation: a possible mechanism of atypical antipsychotic‐induced cortical dopamine release

Abstract: Atypical antipsychotic drugs (APDs), all of which are relatively more potent as serotonin (5-HT) 2A than dopamine D 2 antagonists, may improve negative symptoms and cognitive dysfunction in schizophrenia, in part, via increasing cortical dopamine release. 5-HT 1A agonism has been also suggested to contribute to the ability to increase cortical dopamine release. The present study tested the hypothesis that clozapine, olanzapine, risperidone, and perhaps other atypical APDs, increase dopamine release in rat medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
345
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(366 citation statements)
references
References 49 publications
16
345
1
4
Order By: Relevance
“…Apparently consistent with this possibility, a recent study proposed that risperidone and clozapine could increase DA release in the medial prefrontal cortex (Hertel et al, 1996;Kuroki et al, 1999;Ichikawa et al, 2001). Moreover, these effects of atypical antipsychotics are through D2 and 5-HT2A receptors blockade (Ichikawa et al, 2001). On the other hand, haloperidol has been reported to increase DA release in the nucleus accumbens but not in the medial prefrontal cortex (Kuroki et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Apparently consistent with this possibility, a recent study proposed that risperidone and clozapine could increase DA release in the medial prefrontal cortex (Hertel et al, 1996;Kuroki et al, 1999;Ichikawa et al, 2001). Moreover, these effects of atypical antipsychotics are through D2 and 5-HT2A receptors blockade (Ichikawa et al, 2001). On the other hand, haloperidol has been reported to increase DA release in the nucleus accumbens but not in the medial prefrontal cortex (Kuroki et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
“…Hence, risperidone and clozapine may be able to increase DA release in the medial prefrontal cortex. Apparently consistent with this possibility, a recent study proposed that risperidone and clozapine could increase DA release in the medial prefrontal cortex (Hertel et al, 1996;Kuroki et al, 1999;Ichikawa et al, 2001). Moreover, these effects of atypical antipsychotics are through D2 and 5-HT2A receptors blockade (Ichikawa et al, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the D1 agonist dihydrexidine releases acetylcholine in the PFC and enhances cognitive performance in rats (Steele et al, 1997) and in monkeys (Schneider et al, 1994), effects blocked by SCH 23390. Of interest in this regard is the recent finding that atypical, but not traditional antipsychotic drugs increase cortical acetylcholine release in the PFC with no effect in the nucleus accumbens or striatum (Ichikawa et al, 2002).…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
“…Moreover 5-HT 1A agonists are known to increase cortical DA efflux without affecting striatal DA efflux (Arborelius et al, 1993;Rollema et al, 2000). Ichikawa et al (2001) recently hypothesized that simultaneous blockade of 5-HT 2A and DA D 2 receptors causes an increase in cortical DA efflux by facilitating 5-HT 1A agonist activity by endogenous 5-HT. It may thus be suggested that, by directly activating 5-HT 1A receptors, SSR181507 is functionally equivalent to atypical antipsychotics that indirectly achieve this effect.…”
Section: Mesocorticolimbic Selectivity and Atypical Antipsychotic Promentioning
confidence: 99%
“…Recent preclinical and clinical data have suggested that combining antagonist activity at DA D 2 receptors with agonist activity at 5-HT 1A receptors might offer a promising alternative to schizophrenia treatment (see Meltzer and McGurk, 1999;Millan, 2000;Ichikawa et al, 2001;Bantick et al, 2001 for reviews).…”
Section: Introductionmentioning
confidence: 99%